Recombination between coronaviruses and synthetic RNAs and biorisk implications motivated by a SARS-CoV-2 FCS origin controversy - Mueller, Siguna (Frontiers in Bioengineering and Biotechnology, 2023)
The urgent need for improved policy, regulation, and oversight of research with potential pandemic pathogens (PPPs) has been widely acknowledged. A 2022 article in Frontiers in Virology raised questions, reporting on a 100% sequence homology between the SARS-CoV-2 furin cleavage site (FCS) and the negative strand of a 2017 patented sequence. Even though Ambati and collaborators suspect a possible inadvertent or intentional cause leading to the FCS insert, the related underpinnings have not been studied from the perspective of potential biorisk policy gaps. A commentary on their article contested the low coincidence likelihood that had been calculated by Ambati et al., arguing that the sequence match could have been a chance occurrence alone. Additionally, it has been suggested that the odds of the recombination event may be low. These considerations seem to have put many speculations related to any implied viral beginnings, notably from a research setting likely outside the Wuhan Institute of Virology, to rest. However, potential implications for future disasters in terms of biosafety and biosecurity have not been addressed. To demonstrate the feasibility of the Ambati et al. postulate, a theoretical framework is developed that substantially extends the research orientations implicated by these authors and in the related patent. It is argued that specific experimental conditions combined could significantly increase the implied recombination profile between coronaviruses and synthetic RNAs. Consequently, this article scrutinizes these largely unrecognized vulnerabilities to discuss implications across the spectrum of the biological risk landscape, with special attention to a potential "crime harvest." Focusing on insufficiently understood features of interaction between the natural and man-made world, vulnerabilities related to contaminants, camouflaging, and various misuse potentials fostered by the digitization and computerization of synthetic biology, it highlights novel biorisk gaps not covered by existing PPP policy. Even though this work does aim to provide proof of the viral origin, it will make the point that, in theory, a convergence of under-appreciated lab experiments and technologies could have led to the SARS-CoV-2 FCS, which analogously could be exploited by various threat actors for the clandestine genesis of similar or even worse pathogens.